KOMPOSIT HIDROKSIAPATIT DARI CANGKANG TELUR DENGAN TiO2 SEBAGAI KATALIS DALAM PROSES ADSORPSI METHYLEN BLUE - Lutfiana, Ayu; Cahyadi, Setiawan; Luthfiyah, Luthfiyah; Qolbiah, Iftatun; Jelsy, Jelsy; Putri, Noni Khaisha; Widiyowati, Iis Intan (PROSIDING SEMINAR KIMIA, 2024)
Hydroxyapatite (HAp) is an inorganic compound composed of calcium (Ca) and phosphate (PO43-). This compound is useful for removing colored liquid waste and becomes an environmentally friendly adsorbent. HAp sources are very abundant and have high economic value, one of which is eggshells. Eggshells contain 94% calcite compound, this compound contributes to the mechanical properties and strength of HAp. HAp has unique properties of high ion exchange and adsorption, high thermal stability, and non-toxicity, but there are shortcomings of HAp namely poor mechanical properties and brittleness. A way to improve the mechanical strength of HAp is to composite it with metals. This study was designed to determine the adsorption ability of hydroxyapatite (HAp/TiO2) composite from eggshell against methylene blue. In this study, the synthesis of HAp using hydrothermal method with eggshell material through the calcination process with a temperature of 1000°C obtained the results of CaO which will be synthesized into pure HAp and the results of HAp will be composited with TiO2 metal. The results of HAp/TiO2 are used to adsorb methylene blue with several variations, namely mass, pH, concentration, and time. From the various variations obtained results for the optimum mass variation of 0.125 grams, the optimum contact time at 4 hours, and for the optimum concentration with pH 9, and at a concentration of 100 ppm provides maximum adsorption results against methylene blue. Keywords : Hydroxyapatite; Composite; Adsorption; Methylene Blue